Self-Efficacy and Attitude Mediation in the UMEGA Model: Behavior of e-Samsat Users in Bali - Ni Luh Feby Millennia Yustina; Roekhudin Roekhudin; Rusydi Mohamad Khoiru (Postgraduate Program Merdeka University, 2024)
The aim of this research is to provide empirical evidence regarding the influence of variables in the UMEGA Theory model on taxpayers' behavior intention in adopting the e-Samsat system and to test the role of attitude variables as mediating variables in the UMEGA model. This research also adds self-efficacy as a predictor of behaviour intention to expand the UMEGA model. Sampling in this study used a non-probability sampling technique using purposive sampling. The sample in this study was 411 respondents who were motor vehicle taxpayers in Bali Province. This research uses quantitative method with primary data through distributing questionnaires. Data processing uses Partial Least Square analysis. The research results show that the variables performance expectancy, effort expectancy, social influence and perceived risk influence attitudes. Attitude and self-efficacy variables were also found to influence the behaviour intention of motor vehicle taxpayers. Attitude was found to mediate the relationship between the influence of performance expectancy, effort expectancy, social influence and perceived risk on behaviour intention. Meanwhile, the facilitating condition variable was not found to be a predictor of taxpayers' behaviour intention in using e-Samsat. JEL Classification: M2, O3 DOI: https://doi.org/10.26905/afr.v7i3.13550.